Optimization and Stability Assessment of Chitosan/PVA Smart Sensor Films Incorporated with Roselle Anthocyanins for Real-Time Visual Monitoring of Chicken and Shrimp Freshness under Different Storage Conditions - Hidayaty, Alfianita Nuril; Fiddaroini, Saidun; Fahmi, Ahmad Luthfi; Fardiyah, Qonitah; Sabarudin, Akhmad (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
The development of intelligent packaging systems has become a promising approach to ensure food safety and quality by enabling real-time freshness monitoring. In this study, chitosan/polyvinyl alcohol (Cs/PVA)-based smart sensor films incorporated with roselle (Hibiscus sabdariffa L.) anthocyanins were fabricated and optimized for the visual detection of chicken and shrimp spoilage under variations storage. Anthocyanins were extracted from fresh roselle petals through different maceration periods (R1–R5) to investigate their influence on film properties. Physicochemical characterization revealed that extended maceration enhanced anthocyanin loading, leading to increased film thickness, higher color saturation, and improved optical responsiveness. FESEM micrographs demonstrated homogeneous polymer matrices at lower anthocyanin concentrations, while higher loadings induced micro-aggregates that enhanced volatile adsorption and sensing sensitivity. The fabricated films exhibited clear and progressive color transitions aligned with the spoilage process: red–purple at fresh conditions (pH 5–6), brown–green at intermediate spoilage (pH 7–9), and yellow–brown at advanced spoilage (pH ≥10), consistent with anthocyanin structural transformations. Storage trials with chicken and shrimp confirmed that the Cs/PVA–R5 film displayed the intense coloration and strong response to volatile amines such as ammonia, trimethylamine, and dimethylamine, enabling reliable freshness monitoring. Importantly, the films provided a visual indication when the pH exceeded the edibility threshold of 7.0–7.5, beyond which the samples were deemed unsuitable for consumption. Overall, this work demonstrates the potential of Cs/PVA–roselle anthocyanin films as eco-friendly, low-cost, and effective smart indicators for meat and seafood freshness, offering a practical platform for intelligent food packaging applications.